Crosscurrents : how film policy developed in Quebec, 1960-1983 - Dilley, Constance, 1941- (Culture et publics., 2018)
Crosscurrents: How Film Policy Developed in Quebec 1960-1983 documents the fight by filmmakers in Quebec for a film policy that would support their ambition to create commercial feature films. In the process, it explores the history of Quebec cinema, charting how the government supports that exist today came into existence through an intense lobbying effort on the part of filmmakers. Further, the author describes how cultural bureaucrats colluded with filmmakers to force the government's hand, and outlines the effects of this legislative process on Quebec's English-speaking filmmakers. This volume arises from the author's analysis of voluminous provincial, federal, association, and personal archival sources and also draws on interviews with key figures. The archival sources describe the development over 23 years of provincial structures and policies that try to accommodate the cultural and economic needs of a young, emerging film industry. The result is a book that casts new light on the early events in the cultural life of modern Quebec.